Challenges in collecting sustainability information in Multi-Tier Supply Chains : Impact of EU Corporate Sustainability Due Diligence directive - Naukkarinen, Saara (My University, 2022)
Sustainable supply chain management (SSCM) is becoming increasingly important to companies. The literature has acknowledged that multi-tier supply chains can have a positive impact on sustainability but expanding the scope of SSCM is challenging as it e.g., decreases management efficiency because of information exchange difficulties and because of the restricted observability of supply chain partners. Stakeholders are extensively requiring the companies to extend their sustainability management practices to the entire, complex multi-tiered supply chains and the proposal of the EU Corporate Sustainability Due Diligence (CSDD) directive is a novel example of that. To answer to the requirements of stakeholders and the directive, firms must collect sustainability information from their supply chains, hence are facing several challenges related to multi-tier sustainable supply chain management (MT-SSCM), transparency and due diligence. The purpose of this study is to find out what kind of challenges do companies face in collecting sustainability information in multi-tier supply chains and whether the new EU CSDD would bring any additional challenges to them. The aim of the research is also to see if the industry, the existing regulation affecting sourcing, or the company’s perceived maturity of sustainability management influence the challenges companies face. The research approach for this study is qualitative. Four semi-structured interviews were conducted in companies included in the EU CSDD scope and analysed using thematic analysis. The findings of this research indicate that the challenges companies see emerge mainly from supply chain complexity, which brings challenges, such as lack of power, distance, and lack of visibility, that subsequently influence supplier resistance, transparency, company resources and information gathering. Challenges emerging from the EU CSDD are mainly related to the content of the directive and the extra resources needed for complying with the regulation. The nature of the industry where the company operates, regulation and the company’s subjective perception of their sustainability management maturity affect how challenging companies saw answering to the directive. This research concludes that MT-SSCM, transparency and due diligence literature are closely interlinked and that the challenges in collecting sustainability information affect the success in all the three areas. This study fills in the gap on MT-SSCM literature and is especially concentrating on the relations of transparency and due diligence to MT-SSCM. It is also novel research of the challenges emerging especially from EU CSDD. This study provides business leaders understanding of where the challenges are stemming from and helps them to navigate in the dynamic world of changing sustainability requirements. This study also gives suggestions for policy makers on how to build better regulation.

Vastuullinen toimitusketjujen hallinta (sustainable supply chain management, SSCM) on yhä tärkeämpää yrityksille. Multi-tier -toimitusketjujen positiivinen vaikutus toimitusketjun kestävyyteen on huomattu myös kirjallisuudessa, mutta SSCM:n soveltamisen laajentaminen pidemmälle toimitusketjuun on haastavaa, sillä esimerkiksi vaikeudet tiedonvaihdossa heikentävät hallinnoinnin tehokkuutta ja näkyvyys toimitusketjun ylävirran toimijoihin on huonontunut. Sidosryhmät vaativat enenevissä määrin yrityksiä laajentamaan vastuullisuuden hallintaa koko monimutkaisiin multi-tier -toimitusketjuihin, ja EU:n yritysten kestävää toimintaa koskeva huolellisuusvelvoite (EU Corporate Sustainability Due Diligence, CSDD) -direktiiviehdotus on tuorein esimerkki tästä. Vastatakseen sidosryhmien ja direktiivin vaatimuksiin yritysten on kerättävä toimitusketjujensa vastuullisuustietoa, mikä tarkoittaa niille useita multi-tier -toimitusketjun hallintaan, läpinäkyvyyteen ja due diligencen suorittamiseen liittyviä haasteita. Tämän tutkimuksen tarkoituksena on selvittää, millaisia haasteita vastuullisuustiedon kerääminen multi-tier -toimitusketjuista aiheuttaa yrityksille ja millaisia lisähaasteita he näkevät EU:n CSDD:n heille tuovan. Tutkimuksen tarkoituksena on myös selvittää, vaikuttaako toimiala, hankintaan vaikuttava olemassa oleva sääntely tai yrityksen näkemys omasta vastuullisuuden hallinnan edistyksellisyydestä yritysten kohtaamiin haasteisiin. Tässä tutkimuksessa on käytetty kvalitatiivista tutkimusotetta. Neljä EU:n CSDD:n soveltamisalaan kuuluvaa yritystä haastateltiin ja tulokset analysoitiin teemoittelulla. Haastattelut olivat puolistrukturoituja. Tämän tutkimuksen tulokset osoittavat, että yritysten näkemät haasteet johtuvat pääasiassa toimitusketjun monimutkaisuudesta, joka luo haasteita, jotka liittyvät neuvotteluvaltaan, etäisyyteen ja näkyvyyden puutteeseen, jotka edelleen vaikuttavat toimittajien luomaan vastarintaan, läpinäkyvyyteen, yrityksen resursseihin ja tiedonkeruuseen. EU:n CSDD:n luomat haasteet liittyvät direktiivin sisältöön ja asetuksen noudattamisen edellyttämiin lisäresursseihin yrityksiltä. Yrityksen toimialan luonne, sääntely ja yrityksen subjektiivinen näkemys vastuullisuuden hallinnan edistyksellisyydestä vaikuttavat siihen, kuinka haasteellisena yritykset näkivät direktiivin noudattamisen. Tutkimus osoittaa, että multi-tier -toimitusketjun vastuullisen johtamiseen (MT-SSCM), läpinäkyvyyteen ja due diligenceen liittyvä kirjallisuus liittyvät läheisesti toisiinsa. Se osoittaa myös, että vastuullisuustiedon keräämisen haasteet vaikuttavat kaikkien kolmen osa-alueen tavoitteiden onnistumiseen. Tämä tutkimus pyrkii täyttämään vajeen MT-SSCM -kirjallisuudessa ja keskittyy erityisesti läpinäkyvyyden ja due diligencen vaikutuksiin MT-SSCM:n toteuttamisessa. Se luo myös uutta tutkimusta erityisesti EU:n CSDD:n nouseviin haasteisiin liittyen. Tämä tutkimus antaa yritysjohtajille ymmärrystä siitä, mistä haasteet johtuvat, ja auttaa heitä navigoimaan muuttuvien vastuullisuusvaatimusten maailmassa. Tämä tutkimus antaa myös ehdotuksia poliittisille päättäjille paremman sääntelyn rakentamiseksi.
Keywords: MT-SSCM, multi-tier sustainable supply chain management, sustainability, transparency, due diligence, supply chain management, EU CSDD, EU Corporate Sustainability Due Diligence, supply chain